Keistimewaan Budaya Sunda Ngujuban Pada Masyarakat Kecamatan Maja - Andriyani, Nuri (Jaladri : Jurnal Ilmiah Program Studi Bahasa Sunda, 2024)
The Sundanese cultural tradition of Ngujuban is an activity to honor or bring forth ancestors. There are offerings like food offerings, drinks, market snacks, flowers, cigarettes and prayers. Aims to honor and remember the ancestors, as well as ensuring safety and prosperity for them in the afterlife. This culture contains morals that can be applied in everyday life. This research method uses a qualitative method reinforced by descriptive interviews with several sources from Maja District. The results of this research show that the specialty of Sundanese Ngujuban culture lies in its implementation, namely one day before holidays and celebrations, where karuhun or ancestors come to visit their respective families. There are lessons that can be applied in the form of (1) Educational Values; (2) Religious Values; (3) Social Values; (4) Spiritual Values; and (5) Cultural Values. By discussing Sundanese Ngujuban culture, it is hoped that the Indonesian people, especially Sundanese people who do not yet know about this culture, can become aware of it and use it as learning material regarding the diversity that exists in Sundanese society and that it is widely known and also useful for other communities.